Sex steroid hormones mediate the association between neonicotinoids and obesity among children and adolescents - Qian Su; Jinzhu Luo; You Zhou; Miao Liu; Shaohua Zeng; Yin Li; Jieying Gao (Ecotoxicology and Environmental Safety)
Background: Neonicotinoids are the most widely used insecticide worldwide. Toxicological and epidemiological studies suggest that exposure to neonicotinoid may be linked to the development of childhood obesity. However, the evidence is limited. Objective: To investigate the association between neonicotinoid exposure and obesity among U.S. children and adolescents and to explore underlying mechanism mediated by serum sex steroid hormones in these associations. Methods: Data from the 2015–2016 National Health and Nutrition Examination Survey were used for the analysis. Generalized linear regression was used to investigate the association between detectable neonicotinoids and ten measures of obesity. The interaction effects of multiple neonicotinoids were determined by Chi-squared Automatic Interaction Detection method. Mediation analysis was used to assess potential mediators of sex steroid hormones, including testosterone (T), estradiol (E2), T/E2, sex hormone-binding globulin (SHBG), and free androgen index (FAI). Results: Clothianidin (β = −0.29, 95 % CI: −0.57, −0.01) and N-desmethyl-acetamiprid (β = −0.19, 95 % CI: −0.35, −0.03) were associated with reduced VFI z-score. After stratification, 5-hydroxy-imidacloprid was positively associated with the risk of general obesity in males (OR=2.24, 95 % CI: 1.20, 4.20) with a probability of 52.5 %. FAI mediated 15 % of the association between neonicotinoid exposure and reduced risk of obesity, and SHBG mediated 30 % of the association between neonicotinoid exposure and increased risk of obesity. Conclusion: Neonicotinoids showed associations with obesity, but the results were mixed and sex-specific. Sex steroid hormones may play a role in mediating the effects of neonicotinoids on obesity.